The Influence of Financial Attitude, Financial Knowledge, and Lifestyle on Financial Management Behavior Through Locus of Control as a Moderating Variable in Students in Medan City - Humaira, Alya; Tanjung, Ahmad Albar (International Journal of Management Science and Information Technology, 2026)
The rapid diffusion of digital financial services, e-wallets, and buy-now-pay-later (BNPL) schemes has reshaped how Indonesian university students manage money, yet many still exhibit weak financial management behavior. This study examines the effects of financial attitude, financial knowledge, and lifestyle on financial management behavior, and tests locus of control as a moderator of these relationships among university students in Medan City. Locus of control is positioned as a moderator on theoretical grounds: it reflects individuals’ beliefs about the extent to which outcomes depend on their own actions rather than external forces, and it is therefore expected to influence the strength with which financial attitudes, financial knowledge, and lifestyle translate into actual financial behavior. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Data were collected from 150 university students in Medan City through purposive sampling, with the criteria of being active students who use digital financial services such as e-wallets or PayLater. The results show that financial attitude (β = 0.292; p < 0.001) and financial knowledge (β = 0.282; p < 0.001) have a positive and significant effect on financial management behavior, whereas lifestyle exerts a negative and significant effect (β = -0.291; p < 0.001). However, locus of control does not significantly moderate the effects of financial attitude (p = 0.796), financial knowledge (p = 0.926), or lifestyle (p = 0.703) on financial management behavior. The model explains 62.3% of the variance in financial management behavior (R² = 0.623). These findings imply that universities and policymakers should design financial education programs that jointly strengthen financial attitudes, financial knowledge, digital financial literacy, and self-regulation against consumptive lifestyles, while recognizing that psychological traits such as locus of control may operate through direct rather than moderating pathways in this population.